Job Characteristics Model-based Study of the Intrinsic Incentive Mechanism for Primary Health Workers - ZHAO Shichao, PING Jing, ZHU Hong, JI Wanting, WANG Yuyan, WANG Ying (Zhongguo quanke yixue, 2023)
Background The incentivation for primary health workers is vital for the realization of two goals of the new healthcare reform in China, namely strengthening primary healthcare and achieving hierarchical diagnosis and treatment. Most previous studies put more emphasis on extrinsic incentive measures and their effect on job outcomes, ignoring the intrinsic motivation effect of job itself. Objective To perform an analysis of the job characteristics of primary health workers using the framework of Job Characteristics Model, assess their intrinsic motivation effect on job outcomes of these workers, and compare the strength of impact of the five dimensions of job characteristics and income and other extrinsic motivators on job outcomes, and put forward policy recommendations for improving work motivation and performance of primary health workers. Methods A survey using a self-developed questionnaire was conducted with primary health workers who were on duty on the day of the survey selected from a multistage sample of healthcare settings (including 18 community health centers and 20 township health centers) in three cities of Shandong Province from February to June 2021. Then, from those who effectively completed the survey, 167 cases were selected using convenience sampling to attend semi-structured interviews to understand their views of the characteristics of job as a primary health worker. Pearson correlation was used to analyze the correlations of the five dimensions of job characteristics and extrinsic motivators with autonomous motivation, performance, burnout, and turnover intention. Hierarchical multiple linear regression was used to analyze the strength of impact of the five dimensions of job characteristics and extrinsic motivators on job outcomes. Thematic analysis was used to analyze the interview data. Results A total of 870 cases who handed in effective questionnaires were included for analysis. Among the five dimensions of job characteristics, respondents scored highest and lowest on skill variety (4.09±0.71) and task identity (3.18±1.04) , respectively, and their scores on task significance, feedback from job and autonomy were (3.91±0.76) (3.46±0.83) and (3.43±0.79) , respectively. Pearson correlation analysis showed that the level of each of the five dimensions of job characteristics had a positive correlation with autonomous motivation and performance (P<0.05) , and had a significant negative correlation with burnout and turnover intention (P<0.05) . Hierarchical multiple linear regression revealed that the five dimensions of job characteristics had significant impacts on job outcomes, specifically, autonomous motivation (R2=18.8%) , performance (R2=11.3%) , job burnout (R2=16.5%) and turnover intention (R2=21.9%) , whose explanatory power was stronger than that of five extrinsic motivators (The R2 values of the five extrinsic motivators' contributions to the four job outcomes were 1.7%, 3.4%, 5.8%, and 11.8%, respectively) . The interview results reflected the problems of task fragmentation, limited autonomy and insufficient feedback from job. Conclusion In primary health workers, the intrinsic motivation effect of job characteristics outweighs the extrinsic motivation effect in terms of explanatory power for job outcomes. And there is a gap between actual and theoretical job characteristics. Attention should be paid to the intrinsic motivation effect of job itself. Some measures should be taken, such as increasing training opportunities and quality, reducing work-related burden of these workers and empowering them, increasing resource investment and reducing policy constraints, improving the performance management system, to reshape job perceptions to improve work motivation and performance of primary health workers.